Pegylated-Interferon Alpha 2b and Ribavirin for Recurrent Hepatitis C after Liver Transplantation: From a Canadian Experience to Recommendations for Therapy - Mohamed Babatin; Lynn Schindel; Kelly W Burak (Canadian Journal of Gastroenterology)
BACKGROUND: Recurrent hepatitis C (HCV) after liver transplantation (LT) is often more aggressive and treatments tend to be less successful. Pegylated-interferon and ribavirin are the standard of care for the treatment of HCV; however, there is limited published experience of its use after LT.